Interelasi Subsistem Komunikasi Pemerintah dalam Pengembangan Kambing Kaligesing di Purworejo - Tatag Handaka; Hermin Indah Wahyuni (FISIP Universitas Atma Jaya Yogyakarta, 2017)
Government communication system encounter extension and selling complexity. The aim of the study is to know how interrelation of government communication sub system in encounter extension and selling complexity in Kaligesing goat farming in Purworejo regency. The theory of the study is communication system in perspective of Niklas Luhmann. The study was used explorative case study method. The result of the study showed that extension sub system and breeding sub system not optimal in interrelation. So, information which produced and reproduced not solved complexity effectively.